Risk of Epilepsy in Offspring Exposed to Preeclampsia or Eclampsia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Researchers at the University of Aarhus, Denmark, and at centers in China and US, conducted a population-based study of singletons born in Denmark (1978-2004) with information on preeclampsia and epilepsy obtained from the Danish National Hospital Register.